2013
DOI: 10.1186/1754-6834-6-104
|View full text |Cite
|
Sign up to set email alerts
|

Product inhibition of cellulases studied with 14C-labeled cellulose substrates

Abstract: BackgroundAs a green alternative for the production of transportation fuels, the enzymatic hydrolysis of lignocellulose and subsequent fermentation to ethanol are being intensively researched. To be economically feasible, the hydrolysis of lignocellulose must be conducted at a high concentration of solids, which results in high concentrations of hydrolysis end-products, cellobiose and glucose, making the relief of product inhibition of cellulases a major challenge in the process. However, little quantitative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 73 publications
8
94
0
8
Order By: Relevance
“…Cellobiose is a known inhibitor of cellulases, although there is much debate as to the mechanism of inhibition due to the complexity of the cellulase mixtures and hydrolysis of cellulose (44). Previous studies have shown that cellobiose is more inhibitory to CBHs than to EGs and BGLs and that the presence of CDH can alleviate the competitive inhibition of cellobiose on CBHs by oxidizing cellobiose to cellobionate (45,46). Should the rate of cellobiose conversion to cellobionate be increased by means such as improving CDH production in the F5 ⌬ace-1 ⌬cre-1 ⌬ndvB strain, more cellobiose could be directed to cellobionate, which can possibly relieve the inhibition of cellobiose on cellulase.…”
Section: Discussionmentioning
confidence: 99%
“…Cellobiose is a known inhibitor of cellulases, although there is much debate as to the mechanism of inhibition due to the complexity of the cellulase mixtures and hydrolysis of cellulose (44). Previous studies have shown that cellobiose is more inhibitory to CBHs than to EGs and BGLs and that the presence of CDH can alleviate the competitive inhibition of cellobiose on CBHs by oxidizing cellobiose to cellobionate (45,46). Should the rate of cellobiose conversion to cellobionate be increased by means such as improving CDH production in the F5 ⌬ace-1 ⌬cre-1 ⌬ndvB strain, more cellobiose could be directed to cellobionate, which can possibly relieve the inhibition of cellobiose on cellulase.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of relatively lower cellobiose inhibition towards CBH II was also reported in a comprehensive study on cellobiose inhibition using 14 C-labeled cellulose substrates, conducted by Teugjas and Väljamäe (2013). In that study, it was reported that enzymes from glycoside hydrolase (GH) family 7 were most sensitive to cellobiose inhibition followed by family 6 CBHs and endoglucanases (EGs).…”
Section: Effect Of Beta-glucosidase Addition (Exo-bg Synergism)mentioning
confidence: 82%
“…De acordo com essa classificação, as glicosil hidrolases são divididas em 133 famílias, e as β-glucosidases estão reunidas nas famílias 1 e 3, com representantes nas famílias 5, 9, 30 e 116 (Teugjas & Väljamäe, 2013). Na família 1 estão incluídas as β-glucosidases de arqueobactérias, mamíferos e plantas, sendo algumas também originárias de fungos.…”
Section: β-Glucosidasesunclassified
“…niger apresentou uma produção de 508,0 U g -1 , quando cultivado em farelo de trigo suplementado com sais minerias (Qian et al, 2012 Os valores de pH e temperatura encontrados para a maioria das β-glucosidases de fungos mesófilos estão na faixa de 4,0 a 6,5 e 50 a 65°C, respectivamente (Sorensen et al, 2013). No entanto, uma β-glucosidase produzida por Fomitopsis palustres apresentou temperatura ótima de 70°C, enquanto as β-glucosidases de P. brasilianum, A. niger (N188) e Phanerochaete chrysosporium apresentaram temperatura ótima de apenas 22°C (Sorensen et al, 2013;Teugjas & Väljamäe, 2013). Desse modo, os valores de pH e temperatura ótimos encontrados para a β-glucosidase de C. graminicola são semelhante aos descritos para as enzimas de outros fungos mesófilos.…”
Section: A) B)unclassified
See 1 more Smart Citation